Factors Influencing Health Information Seeking Behaviour on Internet: Case of MBA Students of Africa Nazarene University, Kenya - Kesusu, Josephine; Osano, Dr. Hezron (Global Journal of Health Sciences, 2016)
Purpose: The internet has become a valuable source of information of all kind to everyone but more specifically to the young adults. There is a growing literature on health information seeking behaviours in the developed countries but in Kenya this is a grey area and this study attempted to shed light on this new phenomenon. This study examined health information search from the internet by MBA students, African Nazarene University. Methodology: The study evaluated the characteristics of online health information searchers, prevailing health situation of these individuals, type of information sought and applications. Study participants were the entire population of continuing MBA students of Africa Nazarene University. Data collection instrument was a web based self-administered structured questionnaire emailed to participants. Descriptive statistics was used to describe data. Multiple logistics regressions were used to show relationship of variables. SPSS software was used for the analysis of the data. Results are presented in form of line text, charts, figures and tables. Results: The findings showed majority of the respondents had positive health information seeking behaviour and had good health. Socio-Demographic factors mainly age, gender and income influence health information seeking behaviour online. A high percentage of the respondents discussed information obtained online with a healthcare provider. Unique contribution to theory, practice and policy: This study recommends use of internet by the Government and other healthcare providers as one of the health information dissemination tools.